Integration of Technology into Science Teaching: A Phenomenological Study on the Experiences of the Pre-service Teachers - Memiş, Esra Kabataş; Et, Sümeyra Zeynep; Sönmez, Elif (International Council of Associations for Science Education (ICASE), 2023)
Improvements in science and technology have led to changes in education as well as in many other fields. These changes have made it necessary for today’s individuals to have a set of skills in different fields. One of these fields is technology-related skills. Learning environments that require the use of technology undoubtedly play a key role in raising individuals with technological skills. In this direction, the aim of this research is to study the experiences of pre-service science teachers related to the use of technology within the scope of a course. In this qualitative research, a phenomenological methodology was used to reveal the understandings of preservice science teachers on the experience of integrating technological applications into science teaching. In this context, in-depth semi-structured interviews were conducted with 10 pre-service teachers, about their experiences. As a result of the inductive content analysis, the following four themes, which reflect how the participants interpret the integration of technology in science teaching, were determined in line with the experiences of the participants: The technological tools used in the learning environment and why they are preferred, the necessity of the technological knowledge in the teaching profession, the necessity of the use of technology in the learning environment, and the characteristics of a qualified teacher. Based on the results, the practices for teacher education in the integration of technology in science teaching were discussed. © 2023 International Council of Associations for Science Education (ICASE). All Rights Reserved.
Keywords: Pre-service science teachers; technology; technology literacy